2019
DOI: 10.1111/cod.13396
|View full text |Cite
|
Sign up to set email alerts
|

Contact allergy to isothiazolinones epidemic: Current situation

Abstract: Background Since 2009, an increasing number of published cases of allergic contact dermatitis (ACD) from isothiazolinones in Europe was observed, amounting to an epidemic. However, only few studies have assessed the current situation after changes in European regulation. Objectives To analyze the incidence of isothiazolinone‐related ACD in our area in the last decade. Methods A retrospective study analyzed all patients patch tested in the allergy unit in a tertiary hospital in Spain between January 2010 and Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
2
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 10 publications
1
16
2
4
Order By: Relevance
“…Presenting the largest dataset on patch test results with MCI/MI and MI from Turkey, this study highlights some similarities and differences from previous reports on this topic. First of all, many studies on MCI/ MI sensitization reported a clear female preponderance 10,12,16,26,[35][36][37] and a high percentage of patients aged over 40 years. 26,35,38 The present study, however, shows an almost equal sensitization share in male patients.…”
Section: Discussionmentioning
confidence: 99%
“…Presenting the largest dataset on patch test results with MCI/MI and MI from Turkey, this study highlights some similarities and differences from previous reports on this topic. First of all, many studies on MCI/ MI sensitization reported a clear female preponderance 10,12,16,26,[35][36][37] and a high percentage of patients aged over 40 years. 26,35,38 The present study, however, shows an almost equal sensitization share in male patients.…”
Section: Discussionmentioning
confidence: 99%
“…We wczesnych latach XXI w. zezwolono w Europie na stosowanie samego MI w wyrobach przemysłowych bez limitu zawartości, a w 2005 r. został on dopuszczony jako konserwant kosmetyków w stężeniu do 100 ppm [12] w miejsce dotychczas uczulającej mieszaniny MCI i MI stosowanej w niższym stężeniu (kosmetyki pozostawiane na skórze -7,5 ppm, i zmywalne -15 ppm) [12,13]. Od 2009 r. notuje się jednak znaczący wzrost częstości alergii na izolowany MI.…”
Section: Omówienieunclassified
“…Wprowadzenie ograniczenia stosowania MI w produktach kosmetycznych zmywalnych i wycofanie go z pozostawianych na skórze spowodowało spadek uczuleń. W Hiszpanii po początkowym wzroście uczuleń do 4,5% w 2010 r. i szczycie uczuleń w 2015 r. (18,9%) nastąpił spadek alergii do 3,1% w roku 2019 [13]. W latach 1992--2010 według danych pochodzących z 56 klinik i oddziałów dermatologicznych w Niemczech, Szwajcarii i Austrii (Informationverbund Dermatologischer Kliniken -IVDK) dodatnie reakcje z MCI/MI występowały tylko u 2,3% [21].…”
Section: Omówienieunclassified
“…Recently, an editorial highlighted the lack of communication with the manufacturers of medical devices regarding the labelling of ingredients; this is also true for non‐medical products and underlines the importance of creating a regulation, since manufacturers cannot be depended upon to list the correct composition of a device or product . This case highlights several points for the clinician: (i) airborne allergic contact dermatitis caused by paints often has a chronic character and may display atypical clinical features, mimicking AD, (ii) the MI pandemic allergy has not completely subsided, even if the incidence has markedly decreased since 2015: from 18.9% in 2015 to 7.2% in 2018 and 3.1% in 2019, (iii) stricter regulation of the concentration and proper labelling (regardless of concentration) of isothiazolinones in paints are urgently needed, all the more so when used in children's products.…”
Section: Discussionmentioning
confidence: 99%